2012
DOI: 10.5402/2012/575168
|View full text |Cite
|
Sign up to set email alerts
|

Complications of Intrathecal Baclofen Pump: Prevention and Cure

Abstract: Increasingly, spasticity is managed with surgically implanted Intrathecal Baclofen pumps. Intrathecal Baclofen pump revision surgery unrelated to programmable pump end-of-life is not uncommon, requiring special attention during pre-, intra-, and postoperative management. We aimed to identify and describe complications of Intrathecal Baclofen pump as well as to report avoidance and management of complications. Methods and Materials. Through 2002–2006, at the department of neurosurgery, Henry Ford and Oakwood He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
59
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(61 citation statements)
references
References 14 publications
0
59
0
1
Order By: Relevance
“…7,8 However, this result significantly differed in the 2 groups of patients in which the pump was implanted using different techniques (subcutaneously or under the fascia) and with a different preoperative prophylaxis protocol. The subfascial position resulted in a more protected site that appeared to prevent the risk of infection and skin ulceration, usually one of the first signs of infection in very slim children.…”
Section: Infectionsmentioning
confidence: 59%
See 1 more Smart Citation
“…7,8 However, this result significantly differed in the 2 groups of patients in which the pump was implanted using different techniques (subcutaneously or under the fascia) and with a different preoperative prophylaxis protocol. The subfascial position resulted in a more protected site that appeared to prevent the risk of infection and skin ulceration, usually one of the first signs of infection in very slim children.…”
Section: Infectionsmentioning
confidence: 59%
“…7,9,17 The analysis revealed that the majority of events occurred during the first 12 months after the implant, while the number of patients with a complication related to the catheter decreased in the following years. This might be explained by the fact that a certain time interval is required before the catheter is stabilized.…”
Section: Catheter Problemsmentioning
confidence: 99%
“…[1,2,5,6] Initially, we suspected it to be seroma, so just a compressive dressing was applied. We avoided aspiration fearing that it may introduce infection.…”
Section: Discussionmentioning
confidence: 99%
“…Complications of baclofen pump placement include infection, malfunctioning and refraction to baclofen. [2] They can occur at the time of implantation and throughout the life of the implanted system. Any complication requiring removal or change of implant can be very expensive.…”
Section: Introductionmentioning
confidence: 99%
“…Patients are usually required to undergo either general anesthesia or local anesthesia for pump implantation [4,5].…”
Section: Introductionmentioning
confidence: 99%